1999
DOI: 10.1128/jcm.37.10.3092-3096.1999
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chlamydia trachomatis Prevalence in an Asymptomatic Screening Population: Performances of the LCx and COBAS Amplicor Tests with Urine Specimens

Abstract: This study determined the performances of the LCx (Abbott) and COBAS Amplicor (Roche) tests with urine specimens for the detection ofChlamydia trachomatis in an asymptomatic screening population. Randomly selected women and men (age range, 15 to 40 years) registered in 20 general practices in Amsterdam, The Netherlands, were invited to participate in this study. Urine specimens (n = 2,906; 1,138 specimens from men and 1,717 specimens from women) were tested for C. trachomatis by the COBAS Amplicor (Roche) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Screening programs have become more feasible with the introduction of sensitive DNA detection methods, such as the polymerase chain reaction (PCR) test on urine, and the highly effective single‐dose azithromycin treatment [6,7]. Active case finding and early treatment can prevent the development of sequelae and the transmission of the disease in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Screening programs have become more feasible with the introduction of sensitive DNA detection methods, such as the polymerase chain reaction (PCR) test on urine, and the highly effective single‐dose azithromycin treatment [6,7]. Active case finding and early treatment can prevent the development of sequelae and the transmission of the disease in the population.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 2% boric acid to the urine specimen may prevent the growth of bacteria during mailing and perhaps prevent the degradation of nucleic acid in the sample. 39 Morre et al 40 compared the performance of COBAS Amplicor with LCx using 2 906 mailed, first void urine specimens (1,138 from men and 1,717 from women) from an asymptomatic population (overall prevalence of C trachomatis was 2.9%). The IC results indicated that salud pública de méxico / vol.…”
Section: Nucleic Acid Amplification Assays For Chlamydia Trachomatis mentioning
confidence: 99%
“…However, while lowering the cutoff value in the LCR was necessary to identify all positive pools (1), the first study acknowledged the need to validate the pooling strategy using fresh urine specimens (7). Members of our group recently showed that PCR performs better than LCR for the detection of asymptomatic C. trachomatis infections in urine specimens from both males and females (5).…”
mentioning
confidence: 99%
“…Specimen preparation and C. trachomatis testing were performed according to the instructions of the manufacturer and as described previously (5). For pooled urine specimens the same procedure for C. trachomatis detection was used except that, for pools of five urine specimens, instead of 0.5 ml of urine, five 100-l samples of urine, well mixed, were used (0.5 ml).…”
mentioning
confidence: 99%